Perancangan Bodi Mobil Hemat Energi Tipe Urban Bono Kampar - Saputra, Yudi; Nazaruddin, Nazaruddin; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
When designing a car, it is very important to pay attention to the construction and design of the vehicle. This is useful for getting the security and comfort of users in driving a car. In this study, car body design must have the smallest drag coefficient possible. if the vehicle has a large drag coefficient value, it has a large influence on the efficiency or performance of the vehicle, especially in cars with a large Cd value that will greatly affect vehicle speed. This is useful for minimizing the fuel used, and allows the vehicle to reduce the friction forces caused by air while driving. To get drag coefficients, Computational Fluid Dynamic (CFD) software is used. The software used is Solidworks Flow Simulation. From the results of aerodynamic simulations on four alternative car bodies carried out in this study, the smallest Cd (Coefficient Drag) is the second car body model, which has a Drag Coefficient (Cd) = 0.21Keywords: Car, Aerodynamics, Vehicle Dynamics, Drag Coefficient